Tinnitus suppression by electric stimulation of the auditory nerve - Chang, Janice E.; Zeng, Fan-Gang (Frontiers in Systems Neuroscience, 2012)
Electric stimulation of the auditory nerve via a cochlear implant (CI) has been observed to suppress tinnitus, but parameters of an effective electric stimulus remain unexplored. Here we used CI research processors to systematically vary pulse rate, electrode place, and current amplitude of electric stimuli, and measure their effects on tinnitus loudness and stimulus loudness as a function of stimulus duration. Thirteen tinnitus subjects who used CIs were tested, with 9 (70%) being “Responders” who achieved greater than 30% tinnitus loudness reduction in response to at least one stimulation condition and the remaining 4 (30%) being “Non-Responders” who had less than 30% tinnitus loudness reduction in response to any stimulus condition tested. Despite large individual variability, several interesting observations were made between stimulation parameters, tinnitus characteristics, and tinnitus suppression. If a subject’s tinnitus was suppressed by one stimulus, then it was more likely to be suppressed by another stimulus. If the tinnitus contained a “pulsating” component, then it would be more likely suppressed by a given combination of stimulus parameters than tinnitus without these components. There was also a disassociation between the subjects’ clinical speech processor and our research processor in terms of their effectiveness in tinnitus suppression. Finally, an interesting dichotomy was observed between loudness adaptation to electric stimuli and their effects on tinnitus loudness, with the Responders exhibiting higher degrees of loudness adaptation than the Non-Responders. Although the mechanisms underlying these observations remain to be resolved, their clinical implications are clear. When using a CI to manage tinnitus, the clinical processor that is optimized for speech perception needs to be customized for optimal tinnitus suppression.